Аналог теореми про середнє для многочленів спеціального виду - Трофименко, О.Д. (Український математичний журнал, 2011)
Доказана теорема о среднем для полиномов специального вида. Изучен случай суммы по вершинам правильного многоугольника и, таким образом, получен критерий выполнения уравнения специального вида. A mean value theorem for polynomials of a special form is proved. The case of a sum over vertices of a regular polygon is studied and a criterion for the equation of a special form to be satisfied is obtained.